Disruption of Intestinal Homeostasis Through Altered Responses of the Microbial Community, Energy Metabolites, and Immune System in Zebrafish After Chronic Exposure to DEHP - Jia, Pan-Pan; Junaid, Muhammad; Xin, Guang-Yuan; Wang, Yan; Ma, Yan-Bo; Pei, De-Sheng (Frontiers in Microbiology, 2021)
Di-(2-ethylhexyl) phthalate (DEHP) is ubiquitously reported in global water bodies and exhibits various environmental and human health risks. However, the effects of DEHP chronic exposure on the intestinal microbiota and associated host health concerns in aquatic species are still largely unexplored. In this study, chronic exposure to DEHP at environmental levels significantly increased the body weight, length, and body mass index (BMI), especially in male fish. The microbial community was disrupted with the relative abundance of phylum Firmicutes and genera diversity for Prevotella-7, Deefgea, PeM15, Halomonas, Akkermansia, Chitinibacter, and Roseomonas, which are significantly activated in zebrafish after exposure to DEHP. The height of the gut villus, the thickness of muscularis layer, and the number of goblet cells per villus were significantly decreased, as well as showed differences between female and male zebrafish. Further, the levels of energy-related metabolites in gut tissues were increased, compared to the control group. The expression levels of immune-related genes (interleukin 8, il-8, also referred to as cxcl8a), microbial defense-related genes (lysozyme, lyz, interleukin 10, il-10), and obesity-related genes (aquaporin 8a, aqp8, mucin 2.1, muc2.1, fibroblast growth factor 2, fgf2, and proopiomelanocortin a, pomca) were significantly up-regulated in zebrafish, except the down-regulated expressions of toll-like receptor-5 (tlr-5) and interleukin 1β (il-1β) in the females and pomca in the males, respectively. Importantly, Spearman’s correlation analyses revealed that the levels of metabolites and gene expressions in the gut were closely related to the dominant microbial genera, such as Aeromonas, Deefgea, Akkermansia, PeM15, Mycobacterium, and Rhodobacter. Taken together, chronic exposure to DEHP at environmental levels disturbed bacterial composition accompanied by the altered expressions of intestinal metabolites and the critical immune & intestinal function-related genes, which provided novel insights into DEHP effects on perturbation of gut microbiota and metabolic homeostasis in zebrafish.